Penatalaksanaan kegawatdaruratan bidang urologi; priapismus - Marista, Ardina (Wellness And Healthy Magazine, 2020)
Priapism is an erection of the penis for more than 4 hours without accompanying sexual desire. Priapism is a urology emergency whose complications are erectile dysfunction. Risk factors for Sickle cell anemia, drug use, neoplastic syndromes, trauma, hemodialysis, infection (malaria), toxins (scorpion bites, spiders, neurogenic conditions in perioperative patients under the influence of anesthetics. Priapism is divided into two types, ischemic type (95) %), and non-ischemic type (5%). Management is in the form of operative and non-operative management. In ischemic type non-operative management is in the form of blood aspiration in penile corpora (using 16-18Fr abocath in directions 10 and 2, away from bundle neuravascular complexes (in the direction of at 12 o'clock and urethra towards 6 o'clock), aspiration until bright red blood is found. In the non-ischemic type this therapy is considered to have no effect. Non-ischemic type is not an emergency, the treatment in the form of ice compresses in the perineum.In severe circumstances operative management is required in the form of techniques penile shunt.